Student Work Attitude In Implementing Pastry Practices In The Family Welfare Education Study Program Padang State University - Agustimar, Dina; Zulfikar, Dikki (Universitas Negeri Padang, 2023)
The background of this research is the low work attitude of students of the Padang State University Family Welfare Education Study Program in the Implementation of Pastry Practices. This is assumed to be due to habits when learning online which makes students undisciplined in carrying out practices. The aim of the study was to describe the work attitudes of students in terms of discipline, responsibility, confidence, and concern for Family Welfare Education students. This type of research uses quantitative methods with a descriptive approach. The research population was 2020 Family Welfare Education students who had taken Pastry courses. The research sample is 74 people selected by Total Sampling. The data collection technique uses a questionnaire distributed via the Google form. Data analysis used descriptive analysis by categorizing assessments based on the average score and percentage of ratings. The results showed that the level of work attitude was in the low category, ranging from 65.6 to 90.2 (62.2%).